JEMBATAN ATAU JURANG? BEDAH KRITIS ATAS TUJUH MODEL INTERDISIPLINER DALAM KAJIAN ISLAM (DARI INTEGRASI HINGGA KONFLIK METODOLOGIS) - Muhammad Mahfud; Fadilatul Fauziah; M. Khoiruddin; Solihin; Afifatus Sholeha; Sugiyanto; Abd. Hadi; Titarini; Muhammad Hori (Jurnal Riset Multidisiplin Edukasi, 2026)
Contemporary Islamic studies face new dynamics with the development of modern science. The interdisciplinary approach offers an opportunity to enrich the understanding of Islam but also has the potential to create methodological conflicts. This article examines seven interdisciplinary models in Islamic studies—ranging from integration, interconnection, critical dialogue, synthesis, Islamization of knowledge, critical deconstruction, to epistemological conflict models. Using a literature review approach, this paper explores the strengths, weaknesses, and academic implications of each model. The research findings suggest that the interconnection and critical dialogue models are the most adaptive for the development of modern Islamic studies, while the methodological conflict model tends to sharpen paradigm differences without achieving a common ground. This article concludes that the interdisciplinary approach has the potential to serve as a constructive bridge—provided it is conducted with a dialogical, critical, and non-hegemonic attitude.